Pengaruh Ekonomi Orangtua Dan Motivasi Anak Desa Melanjutkan Studi Di Perguruan Tinggi : (Studi Kasus di Desa Woewolo) - Anjelina Lejo; Damianus Tola; Stefanus H.Gusti Ma (Program Studi Pendidikan Ekonomi, Universitas Flores, 2019)
This study aims to find out: The influence of parents in the economy continue children's studies to college. This type of research is research quantitative descriptive. The population in this study is the children of Woewolo village who will went to college with a population of 50 people. The results of this study shows that the economic influence of parents in continuing their studies to the college level of Flores in Woewolo village, Mauponggo sub-district, Nagekeo District simultaneously known from the determination of53.8% and the remaining 46.2% is influenced by other variable who are not thorough. The partial results show that economic variables parents give a significant effect of 48.9% compared to the interest of children studying at the college level Flores by 27.6%. From the results above it can be concluded that the parents are very capable to pay for children's education to Flores college level, while the level the seriousness of children in learning at college is still very low.